At the drop of a veil - Alireza, Marianne (Houghton Mifflin Company Boston, Massachusetts, 1971)
The true story of a California girl's twelve years in the harem of her husband's Arabian family.
Keywords: Saudi Arabia -- Social life and customs; Manners and customs